STRATEGI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KOTA PEKANBARU DALAM MEMPERTAHANKAN PENGHARGAAN WAHANA TATA NUGRAHA TAHUN 2014 - Nasriyadi "; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Wahana Tata Nugraha in an appreciation which is given by central government to the district whether province or regency for the ability and the role of the people to increase the implementation of city-wide transportation system performance. Pekanbaru city gain the Wahana Tata Nugraha Appreciation for the 10th times in 2014. Research is doing for knowing the Pekanbaru Department of Communication in Information Strategy to maintain the Wahana Tata Nugraha Appreciation in 2014. According to Elitan, there are 3 strategies, which are technology strategy,innovation, and operation. Moreover, some factors that influence Pekanbru to be successful for gaining Wahana Tata Nugraha are medium and infrastructure, coordination, human resources, as well the awareness of the society. This research is using descriptive metode, namely analyze that is trying to give detailed illustration based on the real founding on the field. It is then the presentation data can be described by result of interviewing and observation that will help to get the conclusion. The result of the this research shows Pekanbaru Department Comminication and Information strategy to maintain Wahana Tata Nugraha Appreciation in the year of 2014 is good by using Elitan strategy theories, which are technology strategy, innovation and operation. These theories have given freshness to the society in crossing the way. Key word: Wahana Tata Nugraha, strategy , Organization ( Dishubcominfo ).